Elevated interleukin-12 in progressive multiple sclerosis correlates with disease activity and is normalized by pulse cyclophosphamide therapy. - Comabella, M (1998)
Multiple sclerosis is postulated to be a Th1-type cell-mediated autoimmune disease. We investigated cytokine profiles in patients with progressive multiple sclerosis by using intracytoplasmic staining. We found increased IL-12 production by monocytes and increased IFN-gamma production by T cells in untreated patients as compared with controls. In patients treated with methotrexate, methylprednisolone, or cyclophosphamide/methylprednisolone (CY/MP), only CY/MP treatment normalized the elevated IL-12 production. Furthermore, CY/MP-treated patients had decreased IFN-gamma and increased IL-4, IL-5, and TGF-beta expression. Patients followed prospectively before and after starting CY/MP treatment showed a gradual decrease in IL-12 and IFN-gamma production and an increase in IL-4 and IL-5. In vitro, addition of 4-hydroperoxycyclophosphamide, a metabolite of cyclophosphamide decreased IL-12 production in mononuclear cell cultures. When patients were classified as having active or stable disease, IL-12 production correlated with disease activity. In summary, our results demonstrate a Th1-type cytokine bias in peripheral blood mononuclear cells of untreated progressive MS patients that is reversed by CY/MP treatment and is associated with Th2 and TGF-beta (Th3) type responses. These findings provide a basis for immune monitoring of patients with MS and suggest that treatments that downregulate IL-12 may prove to be beneficial in progressive MS.